ANALISIS KONEKTIVITAS JARINGAN JALAN SEBAGAI ARAHAN PERENCANAAN KAWASAN AGROPOLITAN KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Andiko Putra; Rery novio (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to obtain (1) Hierarchy of road network functions in th agropolitan area planning location of Lareh Sago Halaban District, Lima Puluh Kota District, (2) The level of connectivity between regions in the planning location of the agropolitan area (3) The level of suitability of the agropolitan area based on the LQ value (Location Quotient), and (4) Direction of development in the agropolitan area of Lareh Sago Halaban District, Lima Puluh Kota District. The research method that will be used is quantitative descriptive research using a spatial approach. The data analysis technique used in this study is statistical data analysis. Data analysis is used to calculate road network connectivity index, LQ (Location Quotient) index in the study area. The results of this study can be concluded that, (1) the function of the hierarchy of the road network in the Lareh Sago District of Halaban consists of three, namely: primary collector, secondary collector and local road network, (2) Index of road network connectivity to the Lareh Sago District agropolitan area plan Halaban is alpha 0.361; beta 0,434 and gamma 0,511, (3) Analysis of LQ (Location Quotient) in the agricultural sector in Lareh Sago Halaban District, the LQ (Location Quotient) value of the food crops sector which belongs to the leading sector community which has value> 1 is peanut, cassava , and maize, and (4) Planning of Lareh Sago Halaban District agropolitan area refers to the Lima Puluh Kota Regional Spatial Planning namely wetland agriculture plan, dry land agriculture plan, horticulture plan, and plantation plan.